-6x+2-4x=-38

Simple and best practice solution for -6x+2-4x=-38 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+2-4x=-38 equation:


Simplifying
-6x + 2 + -4x = -38

Reorder the terms:
2 + -6x + -4x = -38

Combine like terms: -6x + -4x = -10x
2 + -10x = -38

Solving
2 + -10x = -38

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -10x = -38 + -2

Combine like terms: 2 + -2 = 0
0 + -10x = -38 + -2
-10x = -38 + -2

Combine like terms: -38 + -2 = -40
-10x = -40

Divide each side by '-10'.
x = 4

Simplifying
x = 4

See similar equations:

| x^3+7x-24=0 | | 8=-4+2x | | X^2-X^2=120 | | x^2-2/5x=4/25 | | √2/√7 | | -6x+2-4x=38 | | 4x+20=x(x-5) | | 9p-24=25-2d | | 12+y=90 | | y^2-6y+2x+11=0 | | 5x+65=10x-10 | | 3.50x+15=32.50 | | 10-5x=-8 | | 5x+7=10x+6 | | 4(x+7)+9=64 | | 50-25X=0 | | 4x+7+9=64 | | 8n+9=n | | 3u-u=12 | | V=y/u | | Uy=-10 | | 10(4x)=640 | | -3u=z | | P(x)=-2/3x^2 | | U/z=y | | -3x-3x+8=-22 | | 2y=4(-3)+14 | | -3(-x-4)=-36 | | 2 = s3– 2 | | 23-2X=15 | | p=2g | | X+8X+28=1 |

Equations solver categories